A system dynamics model of the population dynamics of Oestrus sp. (Diptera: Oestridae) infesting Iberian ibex, Capra pyrenaica. Issue 1 (2nd January 2016) - Pérez, J. M.; Moreno, V.; Navas, J.; Vélez de Mendizábal, N.; Quesada, J. M.; Esteban, F. J.
Abstract: We modelled the population biology of Oestrus sp. parasitising the Iberian ibex ( Capra pyrenaica ), using a system dynamics approach. Levels included in the model were as follows: first-instar larvae, third-instar larvae, pupae and resilient pupae. The values used for flows and auxiliary variables were obtained from the scientific literature, including research on both Oestrus ovis and O . sp.; we assumed that these two species are closely related, both morphologically and from a biological point of view. Simulations provided by our model allowed us to estimate the minimum monthly production of first-instar larvae and thus to establish periodic population dynamics, together with predictions for the number of larval generations. The model predicted 3–4 larval generations per year. The model proved to be very sensitive to minimal changes in a number of variables, especially the first-instar larval production rate. Despite its limitations, this methodology could be a versatile tool for studying the population dynamics of this kind of parasites, and for simulating the effects of control programmes.